Rapid Induction of Ageing Character in Brandy Products – Part III. Influence of Toasting - van Jaarsveld, F.P.; Hattingh, S.; Minnaar, P. (South African Journal of Enology and Viticulture, 2016)
As part of a broader study that investigated techniques for the rapid induction of the needed ageing character in brandy products, the effect of oak wood toasting on quality and chemical composition of oak wood extracts and matured and unmatured pot-still brandy, is reported on. Extracts, prepared from oak chips supplied by a South African cooper, and from commercially obtained oak, and representing different oak types and levels of toasting (i.e. untoasted, light, medium and heavy), were added to 70% (v/v) unmatured pot-still brandy and stored for eight months in glass containers (Schott bottles) at room temperature, or in the case of controls, below 0°C. Matured and unmatured (control) pot-still brandy samples were analysed for wood-derived congeners by means of HPLC and GC. Toasted, as opposed to untoasted oak, gave acceptable extracts, the best overall quality pot-still brandies and generally higher concentrations of volatile (GC-determined) and less volatile (HPLC-determined) wood-derived congeners. Toasting provoked an important separation as indicated by discriminant analysis.